A study on the Impact of Management Information Systems on Quality of Service provided at OCMT - Mohandoss, Karthik; Mastan, Mahammad (International Journal of Psychosocial Rehabilitation, 2020)
The dependency level of the Higher Education Institutions (HEI’s) over the MIS is gradually increasing in the present scenario. This has made us to carry out a research at OCMT (Oman College of Management & Technology) to study the impact of MIS over the quality of service from the perspective of academic and administrative staff members. To establish this study, we developed a survey questionnaire and distributed to the staff of OCMT, Sultanate of Oman via an online survey mechanism. The analysis of survey questionnaire results are submitted to the college for enhancing the quality of the system by considering the indicators and the results.